Keefektivan Penerapan Model Role Playing dan Paired Storytelling terhadap Aktivitas dan Hasil Belajar IPS - Purbiyanti, Elis Dwi; Wasino, Wasino; Nuryatin, Agus (Journal of Primary Education, 2017)
Penelitian ini bertujuan untuk mengetahui perbedaan efektivitas model Role Playing dan model Paired Storytelling terhadap aktivitas dan hasil belajar IPS siswa sekolah dasar. Penelitian ini merupakan penelitian komperasi, dengan desain Pretest-Posttest Comparations Group Design. Sampel penelitian dipilih dengan teknik Random sampling. Sampel penelitian adalah siswa kelas V SDN Sambirejo 01 yang berjumlah 60 siswa, yang di random dibagi menjadi dua kelas yaitu kelas 30 siswa kelas eksperimen dengan model Role Playing dan 30 siswa kelas kontrol dengan model Paired Storytelling. Pengambilan data dilakukan dengan instrumen tes berbentuk pilihan ganda, dan instrumen non tes berupa wawancara tidak terstruktur, observasi, jurnal dan dokumentasi. Berdasarkan hasil analisis observasi aktivitas siswa kelas eksperimen pada setiap aspek aktivitas yang diamati menunjukkan adanya selisih persentase rata-rata skor yang lebih baik dibandingkan dengan kelas kontrol yaitu pada aspek listening activities terdapat selisih 40%, aspek visual activities selisih 23,3%, aspek oral activities 20%, aspek writing activities 6,3%, aspek mental activities 10%, aspek emotional activities 26,6%, aspek motor activities 33,4% dan aspek drawing activities 43,4%. Sedangkan hasil tes hasil belajar menunjukkan rata-rata ketuntasan klasikal pada kelas eksperimen sebesar 96,67%. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa penerapan model Role Playing lebih efektif meningkatkan aktivitas dan hasil belajar IPS pada siswa SD dibandingkan model Paired Storytelling.The objective of this study is to find out the differences in the effectiveness of Role Playing and Paired Storytelling model towards the activities and achievement of social subject of elementary school students. This study was comparations study, with pretest-posttest design Comparations Group Design. Samples were choosen by random sampling technique. The samples were students of V (Fifth) graders of 01 State Elementary School Sambirejo, there were 60 students, who were divided randomly into two classes: 30 students as experiments class taught by Role Playing model and 30 students as control class taught by Paired Storytelling model. Data collection was conducted with multiple choice test instruments, and non-test instruments, in the form of unstructured interviews, observations, journals and documentation. The results of the study showed that the experimental class was better in improving students’ activity and achievement than control class. Based on observation analysis result, students’ activity in the experimental class in every observed activity aspect showed the difference percentage of the average score, experimental class was better than control class, the aspect was in difference of listening activities of 40%, the difference aspects of visual activities of 23.3%, oral activities aspect of  20%, writing activities aspects of 6.3%, mental activities aspects of 10%, emotional activities aspects of 26.6%, motor activities aspects of 33.4% and drawing activities aspects of 43.4%. While, the achievement test results showed an average of the experimental class in classical studt completeness of 96.67%. Based on the result of those study, it can be concluded that the implementation of Role Playing Model is more effective than Paired Storytelling in improving activity and achievement of Social Study of Elementary School Students.